Enhancing yield, quality, and water use efficiency in pomegranate (Punica granatum L.) through organic mulching - MESHRAM, D.T.; SINGH, N.V.; BABU, K.D.; GADDAM, M.K. (Journal of Soil and Water Conservation, 2026)
A field experiment was conducted during the late Hasta Bahar at Solapur, located at 17°10′ N latitude, 74°42′ E longitude, and an elevation of 483.5 meters above mean sea level. The objectives was to evaluate the effects of different organic mulches on yield, fruit quality, and water use efficiency (WUE) of pomegranate (Punica granatum L.) and planted at a spacing of 4.5 × 4.0 meters. Three types of organic mulches i.e. wheat straw, sugarcane bagasse, and safflower stalks were assessed under varying irrigation levels ranging from 0.20 to 0.60 *(ETr), in order to quantify their impact on crop performance and resource use efficiency. The physical, chemical, and hydrological properties of the soil profile at the experimental site were evaluated both before and after the study. Water was applied through a drip irrigation system at levels ranging from a minimum of 0.20*ETr to a maximum of 0.60*ETr under a split-plot design. The crop coefficient (Kc) and wetted area (WA) in percentage for third-year pomegranate trees ranged from 0.18 to 0.70 and 30 to 40%, respectively. Among all treatments, sugarcane bagasse mulch recorded the highest values for plant height, number of flowers, branches, stem diameter, and fruit count. The actual amount of water applied under different organic mulch treatments (20–60% ETr) was lower than the estimated crop water demand due to a reduction in surface evaporation. The actual water requirement (WR) of pomegranate trees varied from 7 to 40 liters per tree per day (Ld-¹t-¹) across different phenological stages. An irrigation level of 0.40 × ETr combined with sugarcane bagasse mulch proved to be the most effective treatment for enhancing growth and water use efficiency in third-year pomegranate trees.